An improved process for the production of highly purified recombinant thaumatin tagged-variants. (15th December 2017) - Healey, Robert D.; Lebhar, Helene; Hornung, Simon; Thordarson, Pall; Marquis, Christopher P.
Highlights: Co-expression of thaumatin and a molecular chaperone increases secretion 2-fold. An optimised purification methodology of recombinant thaumatin is reported. Production of highly purified recombinant thaumatin variants is detailed. Thaumatin variants for thaumatin:receptor interaction studies have been produced. Abstract: The sweetest tasting molecule known is the protein thaumatin, first isolated from the katemfe fruit, Thaumatococcus daniellii . Thaumatin is used in the food and beverage industry as a low-calorie sugar substitute. Thaumatin interacts with taste receptors in the oral cavity eliciting a persistent sweet taste and a bitter, liquorice flavor. Recombinant thaumatin was expressed in Pichia pastoris and through a co-expression strategy with a molecular chaperone, yields of one engineered thaumatin variant increased by greater than two-fold. A detailed purification strategy for thaumatin is reported resulting in a homogenous sample recovered at a yield of 42%. The recombinant thaumatins were extensively characterised using size exclusion chromatography for homogeneity, reversed-phase HPLC for purity (99%), peptide digest LC–MS/MS for sequence determination, and circular dichroism and tryptophan fluorescence spectroscopies for conformational characterisation. These new thaumatin variants are amenable for bioconjugation, providing chemical biology tools for thaumatin:taste receptor interaction studies.